BolA Is a Transcriptional Switch That Turns Off Motility and Turns On Biofilm Development - Dressaire, Clémentine (mBio, 2015)
Bacteria are extremely versatile organisms that rapidly adapt to changing environments. When bacterial cells switch from planktonic growth to biofilm, flagellum formation is turned off and the production of fimbriae and extracellular polysaccharides is switched on. BolA is present in most Gram-negative bacteria, and homologues can be found from proteobacteria to eukaryotes. Here, we show that BolA is a new bacterial transcription factor that modulates the switch from a planktonic to a sessile lifestyle. It negatively modulates flagellar biosynthesis and swimming capacity in Escherichia coli. Furthermore, BolA overexpression favors biofilm formation, involving the production of fimbria-like adhesins and curli. Our results also demonstrate that BolA is a protein with high affinity to DNA and is able to regulate many genes on a genome-wide scale. Moreover, we show that the most significant targets of this protein involve a complex network of genes encoding proteins related to biofilm development. Herein, we propose that BolA is a motile/adhesive transcriptional switch, specifically involved in the transition between the planktonic and the attachment stage of biofilm formation.